2005
DOI: 10.1111/j.1365-2494.2005.00449.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential of imaging spectroscopy as tool for pasture management

Abstract: The use of imaging spectroscopy to predict the herbage mass of dry matter (DM), DM content of herbage and crude fibre, ash, total sugars and mineral (N, P, K, S, Ca, Mg, Mn, Zn and Fe) concentrations was evaluated. The experimental system used measured reflectance between 404 and 1650 nm at high spatial (0AE28-1AE45 mm 2 ) and spectral resolution. Data from two experiments with Lolium perenne L. mini-swards were used where the degree of sward damage or N-fertilizer application varied. Regression models were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…(2002) investigated canopy reflectance of a tropical grass grown under different nitrogen treatments and concluded that remote sensing of canopy chemistry in the visible region might be used to map variation in pasture quality. With herbage grown in pots, Schut et al. (2005) found that imaging spectroscopy can provide a means for assessment of herbage mass of DM and for predicting concentrations of several mineral nutrients in herbage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(2002) investigated canopy reflectance of a tropical grass grown under different nitrogen treatments and concluded that remote sensing of canopy chemistry in the visible region might be used to map variation in pasture quality. With herbage grown in pots, Schut et al. (2005) found that imaging spectroscopy can provide a means for assessment of herbage mass of DM and for predicting concentrations of several mineral nutrients in herbage.…”
Section: Discussionmentioning
confidence: 99%
“…canopy chemistry in the visible region might be used to map variation in pasture quality. With herbage grown in pots, Schut et al (2005) found that imaging spectroscopy can provide a means for assessment of herbage mass of DM and for predicting concentrations of several mineral nutrients in herbage. These findings and methodologies are still pending further evaluation under field conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, spectral data efficiency would be improved by optimization of a wavelength subset in the PLS model. This trial might be the first to use ground-based canopy reflectance data acquisition for forage BM and quality prediction using PLS with selected wavebands, although some similar studies have used fullspectrum data applied to PLS regression (Starks et al 2004;Schut et al 2005;Zhao et al 2007).…”
Section: Forage Biomass and Quality Valuesmentioning
confidence: 99%
“…Ustin et al (2004) also suggested that the use of more spectral information may be desirable when measuring heterogeneous vegetation as was the case in this study. Use of different sensor-detecting reflectance between 404 and 709 nm, and 960 and 1650 nm, were useful in models to predict standing grass herbage, macronutrient content and feeding value suggesting that different parts of the spectra contain additional and valuable information (Schut et al, 2005). However, that work was carried out on mini-swards of Lolium perenne, without grazing, and using a procedure by which pixels with soil and dead material were deleted.…”
Section: Discussionmentioning
confidence: 99%